Magnesium maintains endothelial integrity, up-regulates proteolysis of ultra-large von Willebrand factor, and reduces platelet aggregation under flow conditions - Dong, Jing-fei; Cruz, Miguel A.; Aboulfatova, Khatira; Martin, Cecilia; Choi, Hiuwan; Bergeron, Angela L.; Martini, Sheryl R.; Kroll, Michael H.; Kent, Thomas A. (Thrombosis and Haemostasis, 2008)
Mg ++ regulates endothelial functions and has anti-inflammatory effects. Its effects on thrombosis have been demonstrated, but the mechanism remains poorly understood.We investigated the roles of MgSO4 in regulating the release and cleavage of the prothrombotic ultra-large (UL) von Willebrand factor (VWF) and VWF-mediated platelet adhesion and aggregation.Washed platelets were perfused over cultured endothelial cells from human umbilical cord veins under a shear stress of 2.5 dyn/cm2. Release and cleavage of ULVWF by ADAMTS-13 was measured in the absence or presence of physiological or therapeutic levels of MgSO4. Whole blood or plasma-free reconstituted blood was perfused over immobilized collagen to measure the effect of MgSO4 on platelet adhesion and aggregation. Also studied were the effects of MgSO4 on ristocetin-induced platelet aggregation andVWF-collagen interaction.Maintenance of endothelial integrity required physiological levels of MgSO4, but exogenous MgSO4 showed no additional benefits.Exogenous MgSO4 significantly enhanced the cleavage of the newly released ULVWF strings by ADAMTS-13 and markedly reduced platelet aggregation on immobilized collagen under flow conditions.This effect is likely to be mediated through VWF as Mg++ partially inhibited ristocetin-induced platelet aggregation andVWF binding to collagen.MgSO4 is critical for maintaining endothelial integrity and regulates ULVWF proteolysis and aggregation under flow conditions. These results provide a new insight into additional mechanisms involved with magnesium therapy.
Keywords: Magnesium; endothelium; platelets; ADAMTS-13